PENGARUH KEPUASAN, KEPERCAYAAN DAN KEMUDAHAN TERHADAP LOYALITAS PELANGGAN PT GREAT SEASONS TOURS AND TRAVEL DI KOTA BATAM - Jurnal Ilmiah Manajemen Universitas Putera Batam (Universitas Putera Batam, 2018)
The purpose of this research is to know the effect of satisfaction, trust, choice reduction and habit neither entire nor partial towards customer’s loyalty of PT Great Seasons Tours and Travel. The independent variable in this research are satisfaction, trust and choice reduction and habit and the dependent variable is the customer's loyalty. The population of this research are 1739 Respondent that have joined which is the customer’s from PT. Great Seasons Tours dan Travel at Batam City. The sample in this research are 325 respondents, it was taken by using non probability sampling technique with purposive sampling method. This data research have been tested by using multi regression analysis method and the statistic data indicated valid and reliable. The test result by partially can be concluded that satisfaction, trust and choice reduction and habit are significantly effect to customer’s loyalty. The research result show that simultantly satisfaction, trust and choice reduction and habit effect significantly towards customer’s loyalty.